Caribbean opportunities in ag[r]i-business : global niche sector opportunities for Caribbean agriculture - Ivey, Ian (CCS [Georgetown]GY, 2008)
Provides an overview of the key sub-sectors within agriculture which offer growth opportunities and also an overview of the capabilities and enablers available in the region. Presents a matrix that identifies specific niche opportunity areas for Caribbean countries.